A poesia de Paul Auster - Silva, Egle Pereira da (2014)
This thesis examines Paul Auster s extremely neglected early work: his poetry. Five books were published: Unearth (1974), Wall writing (1976), Effigies (1977), Fragments from cold (1977) and Facing the music (1980), available only at antiquarians and restrective universities libraries in the United States, as well as at the New York Public Library. Studies around Auster s poetic oeuvre are restricted to papers, reviews, translator s introduction, and a thesis that focus on his poetry to produce new analyses and interpretations of Auster s novelistic works. The aim of this thesis is to gather this scattered material and provide new parameters of study around his poetry. Divided into three chapters, the first one maps the literary magazines where Auster published his poems at first, the translations of his poems and critical fortune; the second examines Auster s five books according to three specific topics authorship, language, I and other themes related to them; the third analyzes White Spaces , text considered by the author as the bridge that leads him to prose and in this thesis as a singular writing in which Auster consolidates his literary project, since poetry, previous to prose, yet to come. Maurice Blanchot, Karlheinz Stierle and, principally, Auster, lay the foundation of the investigation. Other theorists who contribute to the understanding of the subject will be called to build the sui generis comparativism put into effect here